Urgensi Perluasan Permohonan Pembubaran Partai Politik di Indonesia - Sri Hastuti Puspitasari; Zayanti Mandasari; Harry Setya Nugraha (Fakultas Hukum Universitas Islam Indonesia, 2016)
This research is to analyze the issues of: first, the urgency of extension of petition of the dispersion of political party in Indonesia. Second, it is related to ius constituendum of the procedure of petition of dispersion in Indonesia. The research method used was the juridical normative method using the philosophical approach, regulation approach, and sociological approach. The result of the research concluded that first: the urgency of the extension of the petition for the dispersion of political party breaking the General Election both in terms of the reason of its petition and the parties involved as the petitioner is in order to create a democratic general election in Indonesia. Second, the procedure of the court session of political party dispersion for doing the violation in general election through 5 phases of court session: 1) examining the introduction to examining the administrative completeness of the petitioner. 2) the further court to listen the petitum of the petitioner; 3), The further court session is to listen the explanation of the one reported; 4) the court of evidence including the document evidence, fact evidence and listen to the witnesses of the experts and other related parties and 5) it is about the court of reading the decision.